Innovations in the Management of Social Initiatives - T. Kopylova; M. Sorokina; L. Kiselyova (Евразийская интеграция: экономика, право, политика, 2019)
Innovations in management of social initiatives are the important direction of companies’ innovative management. The methods of working out and implementing the social initiatives while being of prime practical interest are hardly familiar to Russian business. This paper describes the factors which have negative impact on the quality of these programmes and deals with the technologies of the choice of innovation directions. The stages of socially responsible programmes planning and realization are described, the methods to assess the effectiveness of programmes are given, the forms of stakeholders’ dialog in the framework of such programmes working out and implementing are revealed.